Effect of Different Bio Fertilizers on Yield Of Spring Rice (Oryza Sativa L.) CV. Hardinath-1 in Rajapur Municipality, Bardiya (SAARC Journal of Agriculture, 2021)
A field experiment was carried out at Rajapur, Bardiya Nepal to determine the effect of different biofertilizers on the yield of spring rice (Oryza sativa L.). Five different combinations of biofertilizers and chemical fertilizer viz. T1 (Azolla + N:P:K @50:15:15 kg ha-1), T2 (Azotobacter+ N:P:K @50:15:15 kg ha-1), T3 (Azotobacter +Mycorrhiza + N:P:K @50:15:15 kg ha-1), T4 (Azotobacter + Phosphorus Solubilizing Bacteria+ Potassium Mobilizing Bacteria+ N:P:K @50:15:15 kg ha-1) and T5 (Recommended chemical fertilizer i.e. N:P:K @100:30:30 kg ha-1) was used. The experiment was laid out in a simple RCBD design with four replications and 3mˣ2m individual plot size. The hardinath-1 variety was used for the experiment. Biometrical observations like plant height (99.92 cm), number of tillers (355.62 m-2) were found significantly highest in T1 (Azolla + NPK@50:15:15 kg ha-1). Similarly, yield attributing characters such as the number of effective tillers (340 m-2), number of filled grains per panicle (114.30), highest panicle length (28.42 cm) was found significantly the highest in T1 (Azolla + NPK@50:15:15 kg ha-1). The highest grain yield (8.46 ton ha-1), straw yield (12.6 ton ha-1), and harvest index (0.40) were also observed on T1 (Azolla + NPK@50:15:15 kg ha-1). Benefit cost ratio was also found highest on T1 (Azolla + NPK@50:15:15 kg ha-1) which was 2.05 incurring the cost of cultivation Rs 72035 per hectare returning the total revenue of Rs 148190 per hectare. The study shows that the application of T1 (Azolla + NPK@50:15:15 kg ha-1) was the best fertilizer combination for spring rice production as it was superior over other fertilizer combinations in terms of yield and yield attributing characters with the highest benefit cost ratio.SAARC J. Agric., 19(1): 57-69 (2021)